RADIO LOOPS IN ZONE OF AVOIDING OF OPEN CLUSTERS - Shatsova, R. B.; Gozha, M. L. (Одеські астрономічні публікації, 2008)
New catalogues have confirmed the existence of open clusters avoiding zone in the Sun's vicinity. Originally the zone has been found out by Shatsova & Anisimova in 1990. The zone is filled with the radio loops I - IV, the loops opened later and HI areas. Probably the system of open clusters forms a spatial lattice of the density waves. Internal parts of the loops are inside its cells. Shells are limited by the crests of waves.